From Critical Reading to Academic Writing: A Qualitative Case-Study of Reading-to-Writing Transfer in an EFL Classroom - Venny Eka Meidasari; Hanna Sundari; Rina Husnaini Febriyanti; Mashadi Said (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2026)
The ability to transform insights from reading into academic writing is a key component of academic literacy in higher education. However, many English as a Foreign Language (EFL) learners experience difficulties transferring critical reading practices into their written work. However, while previous studies have examined source integration and synthesis in writing, fewer studies have investigated how learners’ actual reading practices shape the transfer of knowledge into writing. This study explores how EFL students in university perceive critical reading and how their reading practices are reflected in their academic writing. Using a qualitative case study approach, the research involved four students enrolled in an academic reading and writing course. Data were collected through structured interviews, annotated reading documents, and students’ academic writing products. The analysis employed thematic analysis and cross-case comparison to examine patterns of reading-to-writing transfer. The findings reveal that while participants demonstrated strong conceptual awareness of critical reading, their enacted reading practices tended to focus on surface-level textual features such as structure, organization, and linguistic forms. These reading behaviors were reflected in their writing, where the transfer from reading to writing occurred primarily through structural imitation and citation practices rather than deeper synthesis of sources. The results highlight a differentiated model of transfer, ranging from surface-level reporting to genre-oriented transfer, integrative framing, and emerging synthesis.